2014
DOI: 10.1017/s0010417514000280
|View full text |Cite
|
Sign up to set email alerts
|

Ilkhanid Buddhism: Traces of a Passage in Eurasian History

Abstract: Buddhism contributed to the culture and politics of thirteenth-century Eurasian intellectual exchange, depositing literary, artistic, and architectural traces subsequently eclipsed by layers of Islamic and Eurocentric history. Within extensive cross-continental networks of diplomatic and commercial activity, Ilkhanid Buddhism and the Buddhist revival of which it was a part drew serious attention among contemporary travelers, scholars, and statesmen including Ibn Taymiyah, Roger Bacon, and Rashid al-Din. This a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 28 publications
(4 reference statements)
0
2
0
1
Order By: Relevance
“…Burgan (2009) explained that when Ghazan was a king, many Mongols converted to Islam. Furthermore, Prazniak (2014) showed that Ghazan started his authority with a wave of persecution against Christians and Buddhists, although he later stopped the forced conversion. Some Mongols also gave up their nomadic lifestyle and started marrying the locals, especially the Turks.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Burgan (2009) explained that when Ghazan was a king, many Mongols converted to Islam. Furthermore, Prazniak (2014) showed that Ghazan started his authority with a wave of persecution against Christians and Buddhists, although he later stopped the forced conversion. Some Mongols also gave up their nomadic lifestyle and started marrying the locals, especially the Turks.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…But if it still did, notwithstanding the fact that bandaqi was not necessarily a rock-cut architecture, we are permitted to believe it did not, because of probabilities referring bandaqi to any brick-based construction in the historic fabric of the Sultaniyya plateau. Moreover, Rashīd al-Dīn's description could only point to a focus on the population in the Ilkhanid Capital, Sultaniyya, where the Buddhist community exists (Prazniak 2014).…”
Section: Why Dash Kasan Cannot Be a Buddhist Monasterymentioning
confidence: 99%
“…36 Hülâgü, Phag-mo-gru-pa Okulu'na mensup yüksek din adamlarına hediyeler göndermiş 37 ve daha sonra İran' daki hükümdarlığı sırasında Tibet coğrafyasındaki iktidarını korumak için Tibet ve Keşmir' e de yürümüştür. 38 Phag-mo-gru-pa, o zamanlar Merkezî Tibet'te önemli bir siyasi ve dini güce sahip olduğundan, Hülâgü'nün maddi ve askeri desteği, bu okul ile Çin Moğolları himayesi altında olan Sa-skya-pa Okulları arasındaki iktidar mücadelesinde önemli bir etken olmuştur. Dolayısıyla Phag-mogru-pa'nın takipçileri Tibet'ten İran'a taşınmış, Uygur, Çin, Tangut tarikatlarına giderek egemen olmuş ve İran' daki Moğollar arasında Tantrik Budizmini yaymıştır.…”
Section: Budizm Ve Moğollardaki Bazı Budist Okullarıunclassified